A perífrase conjuncional só que: gramaticalização e variação linguistica - Luiza Francisca Ferreira da Silva (2017)
The conjunctional periphrasis só que of the Brazilian Portuguese language is theresult of a grammaticalization process, in which lexical categories become grammatical, orgrammatical categories become even more grammatical. In this case, grammaticalization wasresponsible for joining the denotative exclusion word só and the integral conjunction que.This conjunctional periphrasis or adversative conjunctive locution within the grammaticaltradition is in a process of variation with the adversative conjunction but. Both can act asmarkers of expectation breach and co-occur in this function, since they have the same truthvalue. We will define the breach of expectation as the cancellation of information previouslygiven by the speaker, by adding new information, which breaks the assumption created in thefirst message. In this work, from a Labovian perspective, we elaborated a quantitative analysisof the occurrences of só que, comparing them with those of mas, based on 36 recordings ofspontaneous speech performed with 40 speakers of the dialect of Minas Gerais, mostlyresidents of the city of Belo Horizonte. In this study, it was possible to point out sometendencies, such as the fact that, because it is more used by educated speakers, it is a form thatis not socially stigmatized. It is also worth remembering that the corpus used in this researchbelongs to the C-Oral-Brasil I project, from the Faculty of Letters of the Federal University ofMinas Gerais (UFMG).